NILAI MORAL TRI HITA KARANA DALAM ALBUM “KERAMAT” CIPTAAN H. RHOMA IRAMA - Harefa, Darmawan; I Made Sutajaya; I Wayan Suja; Ida Bagus Made Astawa (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2024)
The purpose of this study is to characterize Tri Hita Karana's moral principles as they appear in the H. Rhoma Irama album "Keramat". This study use content analysis as a qualitative tool. The findings of this study demonstrate that there are five moral values: (1) the value of honesty; (2) the value of discipline; (3) the value of caring for others and paying attention to them; (4) the value of respecting others; and (5) the value of fairness. Therefore, it may be claimed that one of the moral precepts present in the lyrics of many sacred songs is the moral precept of respect for other people. Suggestions (1) Teachers and music enthusiasts can learn a lot from this about overcoming obstacles in life. In addition, this holy song by H. Rhoma Irama has significant queries for all of us since it highlights how crucial it is for kids to obey their parents, particularly the mother who gave birth, reared, and took care of us all. The researcher proposes that listeners and admirers of this song should incorporate the five moral principles into their daily lives so that they can safeguard others no matter where they are; (3) the purpose of this research is to encourage readers to delve deeper into other albums to find more inspiration. It also serves as a resource for other scholars who bring up pertinent study topics.